Calidad de servicio al cliente en la línea aérea Latam de la ciudad de Iquitos, año 2019 - Rengifo López, Solange (2021)
The objective of the research was to determine the characteristics of the quality of customer service in the LATAM airline of the city of Iquitos, year 2019. The methodology was quantitative, with a non-experimental research design, descriptive cross-sectional. The population and sample consisted of 150 clients in the LATAM airline of the city of Iquitos, period 2019, being a non-probabilistic sampling. The survey technique was applied; a questionnaire of 22 questions was used as an instrument to collect the information for the variable under study of service quality structured in the dimensions: tangible elements, reliability, responsiveness, security and empathy through a Likert-type scale. The result of the descriptive analysis of the tangible element dimension describes 98% who felt satisfied with the quality of service they received and only 2% qualified as dissatisfied. In the negative stress dimension, 73% of the sample is characterized with a diagnosis of moderate and acute stress (being negative stress or distress) and 27% with functional stress (positive stress or eustress). We conclude that 59% express satisfaction with the quality of service they have received in all its aspects, 30% are very satisfied and only 10% rate it as dissatisfied.